Produksi Enzim Spesifik Xilanase pada Variasi Suhu Konsorsium Trikultur Bakteri Termofilik - Armiliandi, Rada; Irdawati, Irdawati (MASALIQ, 2024)
Xylanase is an extracellular enzyme that is capable of hydrolyzing xylan (hemicellulose) into xylose and xylo-oligosaccharides. Xylanase can be produced by microbes through a fermentation process, the microbes used are thermophilic bacteria. Thermophilic bacteria are microorganisms that are capable of producing thermostable enzymes through fermentation. The bacteria used are MSS11, MS 16 and MS 18. These thermophilic bacteria can live at temperatures above 45°C-80°C. To determine specific enzyme activity, enzyme and protein activity values were tested using a 540 nm (enzyme) and 750 nm (protein) septovotometer. The method used in this research is descriptive in triplicate. The research was carried out at the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Padang State University on December 23 2023. Beechwood medium which had been mixed with MSS 11, MS 16, and MS 18 bacteria was then incubated at temperatures of 55℃, 65℃ and 75℃ so that specific enzyme activity was obtained. Of these three temperatures, the optimum specific enzyme activity of xylanase is 65℃, where the specific enzyme value obtained at 65℃ is 3.31 U/mg. Meanwhile, at low temperatures, namely at 55℃, the enzymatic reaction is slow, namely it has an enzyme activity value of 1.02 U/mg. Finally, at a temperature of 75, there was a decrease in specific enzyme activity, where the specific enzyme activity value was 3.12 U/mg.